Ethical leadership and its importance for food safety at university education - Navarro-Falconí, Julio C. (2023)
This paper highlights the importance of promoting the development and formation of ethical leadership at university students, so that it can help to favorably face the challenges that currently concern countries and that are constituted as the Sustainable Development Goals (SDG). This qualitative research seeks to find the knowledge about ethical leadership, its associated values and the identification of current society that undergraduate students of Le Cordon Bleu university have. For that purpose, a semi-structured questionnaire was applied through Google Forms platform and the analysis of the answers of a population of 45 students from five careers and five different cycles were made, being intentionally selected, with an average age of 24 years, being 19 men and 26 women. The research revealed the assessment that students have about food security and the need to take action to contribute to the reduction of hunger and poverty and the improvement of nutrition and the well-being of society.